Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/molecules27072069
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic CO2 Reduction Using TiO2-Based Photocatalysts and TiO2 Z-Scheme Heterojunction Composites: A Review

Abstract: Photocatalytic CO2 reduction is a most promising technique to capture CO2 and reduce it to non-fossil fuel and other valuable compounds. Today, we are facing serious environmental issues due to the usage of excessive amounts of non-renewable energy resources. In this aspect, photocatalytic CO2 reduction will provide us with energy-enriched compounds and help to keep our environment clean and healthy. For this purpose, various photocatalysts have been designed to obtain selective products and improve efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 144 publications
(127 reference statements)
0
13
0
Order By: Relevance
“…Methane selectivity with improved activity by the formation of heterojunctions has been ascribed to extended light absorption, increased CO 2 adsorption and efficient separation and transfer of light induced carriers. 132 All the TiO 2 based Z-scheme heterojunction composites for photocatalytic CRR have been summarized by Rehman et al 138 However, the formation of heterojunctions is sometimes controlled by the exposed facet. This has been observed in a first principles calculation DFT study, where the (001) and (101) facets were found to be favourable for formation of the heterojunction.…”
Section: Photocatalytic Materialsmentioning
confidence: 99%
“…Methane selectivity with improved activity by the formation of heterojunctions has been ascribed to extended light absorption, increased CO 2 adsorption and efficient separation and transfer of light induced carriers. 132 All the TiO 2 based Z-scheme heterojunction composites for photocatalytic CRR have been summarized by Rehman et al 138 However, the formation of heterojunctions is sometimes controlled by the exposed facet. This has been observed in a first principles calculation DFT study, where the (001) and (101) facets were found to be favourable for formation of the heterojunction.…”
Section: Photocatalytic Materialsmentioning
confidence: 99%
“…24,25 In general, TiO 2 is considered as an ecologically friendly and has been used in various industrial applications including gas sensors, 26 corrosion protection, 27 white pigment, 28 dye-sensitized solar cells, 29 remediation of the environment, 30 hydrogen gas production, 31 providing high dielectric constant and high electrical resistance, 32 and reduction of carbon dioxide. 33 Titanium dioxide NPs can be synthesized using a variety of methods, including sol−gel, sono-chemical, microwave-assisted, 34 deposition, hydro/solvothermal, and oxidation methods. 30,35 Biosynthesis of titanium dioxide NPs has gained wide attention among scholars due to its cost-effective, eco-friendly, and reproducible method.…”
Section: Introductionmentioning
confidence: 99%
“…8 TiO 2 is an extensively studied n-type semiconductor with excellent photocatalytic activity and chemical stability. [9][10][11] In earlier research on PFC, TiO 2 was loaded on the FTO glass as a photoanode by the blade coating method or the solgel method to construct a film electrode, which had outstanding photoelectric conversion efficiency and cycle stability. 12 However, the application of pure TiO 2 is severely restricted by its low quantum efficiency and narrow light absorption range.…”
Section: Introductionmentioning
confidence: 99%